Efecto combinado de cepa de levadura y Terroir en vinos Malbec de Mendoza = Combined effect of yeast strains and Terroir on Malbec wines from Mendoza - Perez, Maria Dolores; Capaldi, Carolina; Mercado, Laura Analia; Malizia, Adriana; Sari, Santiago Eduardo (E3S Web of Conferences, 2020)
Publicado en: E3S Web of Conferences 50 : article number 02005 (2018)